Monospot: a differential slide test for infectious mononucleosis. Issue 3 (May 1969) - Basson, Vivian; Sharp, A. A.
Abstract : Sera collected from 372 patients with suspected infectious mononucleosis were examined for heterophile antibodies by the Paul-Bunnell and the Monospot test. Comparison of results showed the latter to be simple, time saving, and of sufficient specificity for routine use in the general laboratory.